2020
DOI: 10.1155/2020/6181630
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy Triggered by Oxidative Stress Appears to Be Mediated by the AKT/mTOR Signaling Pathway in the Liver of Sleep-Deprived Rats

Abstract: Sleep deprivation adversely affects the digestive system. Multiple studies have suggested sleep deprivation and oxidative stress are closely related. Autophagy can be triggered by oxidative stress as a self-defense strategy to promote survival. In this study, we investigated the effects of sleep deprivation on liver functions, oxidative stress, and concomitant hepatocyte autophagy, as well as the associated pathways. Enzymatic and nonenzymatic biochemical markers in the serum were used to assess hepatic functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 46 publications
5
17
0
Order By: Relevance
“…LC3 (microtubule-associated protein light chain 3, MAP LC3) was the first autophagosome marker protein to be identified in mammals and is homologous to the yeast autophagy-related gene Atg8. Similar to previous studies, SD has been shown to cause excessive levels of autophagy and may be one of the causes of impairment of learning and memory (8,29,30).…”
Section: Discussionsupporting
confidence: 83%
“…LC3 (microtubule-associated protein light chain 3, MAP LC3) was the first autophagosome marker protein to be identified in mammals and is homologous to the yeast autophagy-related gene Atg8. Similar to previous studies, SD has been shown to cause excessive levels of autophagy and may be one of the causes of impairment of learning and memory (8,29,30).…”
Section: Discussionsupporting
confidence: 83%
“…Previous studies have demonstrated that the excessive lipid accumulation can lead to cellular injury and death (Czaja, 2016;Li et al, 2020). In this study, we focused on the effects of dapagliflozin on hepatic steatosis and explored the relevant mechanism using hepatic cells and ZDF rats with obesity, NAFLD and metabolic dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, POMC is one of the target genes of mTOR in the CNS (Cota et al, 2006). A recent study found that sleep deprivation could induce oxidative stress mediated by the AKT/mTOR signaling pathway in the liver of rats (Li et al, 2020). Our study is the first to highlight mTOR signaling dysfunction in the hypothalamus of chronically sleep-restricted rats.…”
Section: Discussionmentioning
confidence: 55%